Efektivitas Antibakteri Ekstrak Daun Sisik Naga (Drymoglossum piloselloides) Terhadap Bakteri MRSA (methicilin resistant Staphylococcus aureus) dan Eschericia coli - Wirjatmadja, Roeswandono; Kurniasari, Putri Nadia Indah; Wibisono, Freshinta Jellia; Kurnianto, Ady (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
The purpose of this research aimed to determine the antibacterial effectiveness of the methanolic extract of dragon scales leaves (Drymoglossum piloselloides) against MRSA (Methicilin-resistant Staphylococcus aureus) and Eschericia coli bacteria in vitro using the diffusion method. This research used a population of Methicillin-resistant Staphylococcus aureus and Eschericia coli bacteria. The sample to be used is dragon scale leaf methanol extract. The method in this research used experimental with 6 treatments, namely dragon scale leaf methanol extract with concentrations of 45%, 55%, 65%, 75%, negative control (methanol) and positive control (chloramphenicol antibiotics). Data collection in this study was carried out by recording the diameter of the inhibition zone using a caliper (mm). The data obtained from the diameter of the inhibition zone of 75% extract variation resulted in an inhibition zone of 17.02 mm (in MRSA) and 8.47 mm (in E.coli). Chloramphenicol was found to be resistant to MRSA, but sensitive to E.coli. Data analysis used ANOVA test which statistically showed that there was a significant difference (P<0.05) in the diameter of the inhibition zone of the dragon scale leaf methanol extract against MRSA bacteria and there was a very significant difference (P<0.01) in the diameter Inhibition zone of dragon scale leaf methanol extract against Eschericia coli bacteria.